2019
DOI: 10.1371/journal.pone.0220900
|View full text |Cite
|
Sign up to set email alerts
|

Small changes, big gains: A curriculum-wide study of teaching practices and student learning in undergraduate biology

Abstract: A growing body of evidence has shown that active learning has a considerable advantage over traditional lecture for student learning in undergraduate STEM classes, but there have been few large-scale studies to identify the specific types of activities that have the greatest impact on learning. We therefore undertook a large-scale, curriculum-wide study to investigate the effects of time spent on a variety of classroom activities on learning gains. We quantified classroom practices and related these to student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…STEM education has evolved into a meta‐discipline, an integrated effort that removes the traditional barriers between these subjects and instead focuses on innovation and the applied process of designing solutions to complex contextual problems using current tools and technologies (Kennedy & Odell, 2014). It is believed that the STEM education can contribute to increased problem‐solving skills, critical thinking and analytical thinking in students and lead to better real‐world connection in the curriculum (Gottesman & Hoskins, 2013; Weir et al., 2019). Meanwhile, it was reported that CBL allows the nursing student to feel more connected to reality and decide how to plan and deliver patient care (Gholami et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM education has evolved into a meta‐discipline, an integrated effort that removes the traditional barriers between these subjects and instead focuses on innovation and the applied process of designing solutions to complex contextual problems using current tools and technologies (Kennedy & Odell, 2014). It is believed that the STEM education can contribute to increased problem‐solving skills, critical thinking and analytical thinking in students and lead to better real‐world connection in the curriculum (Gottesman & Hoskins, 2013; Weir et al., 2019). Meanwhile, it was reported that CBL allows the nursing student to feel more connected to reality and decide how to plan and deliver patient care (Gholami et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…CBL can assist nursing students to integrate and apply the knowledge, skills, judgment and personal attributes required to practise safely and ethically in a designated role and setting (Dubey & Dubey, 2017; Raurell‐Torredà et al., 2015). Increasing evidence suggests that CBL and STEM education have positive effects on critical thinking in undergraduate students, undergraduate mentors, graduate nurses (Gottesman & Hoskins, 2013; Li et al., 2019; Weir et al., 2019; Yoo & Park, 2014). However, less evidences can be found on the effects of teaching reform on a nursing course based on STEM education concept, particularly in mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…Also it is an important segment to promote the "first-class" undergraduate construction of functional materials specialty. Assessment and evaluation is a necessary means, which purpose is to establish a scientific and reasonable evaluation mechanism, and improve students' enthusiasm, and urge students to delve deeper in the process of the internship (Weir et al, 2019). At the same time, the instructors can keep abreast of the students' mastery of the internship content and then provide targeted guidance.…”
Section: Innovative the Evaluation Mechanism Of Cognition Practicementioning
confidence: 99%
“…The COPUS was originally recommended for use by faculty because it could provide the necessary "information to report about their use of active-learning strategies" (Smith et al, 2013, p. 626). Further, it has been implied that efforts to improve undergraduate STEM instruction will facilitate a progression from didactic instructional profiles to student-centered profiles, with interactive lecture profiles as intermediate steps in the progression (Lund et al, 2015;Holland et al, 2018;Stains et al, 2018;Weir et al, 2019). As the Stains and colleagues' study points out, this progression has the potential to "inform incremental and diverse paths toward student-centered teaching" (Stains et al, 2018(Stains et al, , p. 1470.…”
Section: Introductionmentioning
confidence: 99%